Archaeology and the State We're In: Defining a Role for Historic England in the Archaeological Practice of the Twenty-First Century. (3rd April 2018) - Trow, Steve
Abstract: The conduct of archaeology in England has changed radically over the last quarter century, particularly as a result of the introduction of development-led funding. It continues to evolve, not least because of the significant – and in all probability permanent – reductions that have occurred in the UK's public expenditure since 2007–2008. Further change may be anticipated as a result of the UK's exit from the European Union. The creation of Historic England in 2015 has offered an opportunity to review its future role in a national archaeology that is now dominated by the commercial sector, with all the strengths, weaknesses, opportunities and threats that this involves. This article summarises the outcomes of our review and the way Historic England's approaches to archaeological practice will develop as a result. It also provides a more personal perspective on the background to those deliberations. During the review process, Historic England was aware that others were also considering the future of the discipline from different vantage points. These commentators included the British Academy, which chose to address archaeology in the second of its Reflections on Disciplines exercises, and various European archaeologists who were engaged in debate over practice models with differing degrees of state control or commercial freedom.